Almost a century later, the description of the second species of Hebardinella Chopard, 1932 (Orthoptera: Trigonidiidae), and the first record of the genus in Brazil - Santos, Luiz Augusto Padilha; Fernandes, José Antônio Marin; Tavares, Gustavo Costa (Zootaxa, 2026)
Hebardinella Chopard, 1932 is a genus of trigonidiine crickets with a single species, Hebardinella americana (Chopard, 1912), recorded only in French Guiana. They are small and green crickets that lack a stridulatory apparatus on the male tegmina (forewings). They are also characterized by a very short and expanded terminal segment of the maxillary palps and a very wide tympanal opening, which is present only on the inner face of the fore tibia. Here, we describe a new species for the genus, Hebardinella pilimaculata sp. nov., representing the first record of the genus in Brazil.